Development of Android-based Interactive Learning Media on Statistics - Aziz, Abdul; Amidi, Amidi (Unnes Journal of Mathematics Education, 2021)
The purpose of this study is to develop and test the feasibility of android-based interactive learning media based on the feasibility of the validator's assessment from the material side and the media side. This type of research is R&D (research and development). The procedure used in this research and development is the procedure from Borg & Gall, which has been modified by the Puslitjaknov Team using three stages out of 5 stages, namely conducting a needs analysis to be developed developing initial products, and product validation and revision. The product of this research was assessed qualitatively, namely on a 5-point scale ranging from 1 to 5. So, the Likert scale was used for evaluation. This study resulted in an android-based interactive learning media that has been declared valid and feasible to be used as mathematics learning media by five validators from the material side who obtained an average score of 3.75 (good category) and five validators from the media side with a score an average of 3.64 (good category) with each maximum score of eligibility is 5. So, it can be concluded that the android-based interactive learning media developed is valid and feasible to be used as a mathematics learning media.